The Therapy and the Therapist - Morteza Abdoljabari (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Life and health are the greatest divine blessings given to human, and medical sciences have also a great responsibility to protect and maintain the health. In the shadow of benefiting from health, welfare and comfort  will be received in life. Those who gain medical knowledge have high respect in the society.For downloading the full-text of this article please click here. Please cite this article as: Abdoljabari M. The Therapy and the Therapist. J Res Relig Health. 2017; 3(1): 1- 4